Buzzer's Position In Positive Law According To Law Number 11 Of 2008 Concerning Information And Electronic Transactions - Hermanto N, Nestor; Kusno, Kusno; Toni, Toni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study aims to find out and analyze the position of the buzzer who spreads hoaxes in the perspective of positive law. As well as knowing and analyzing criminal responsibility for spreading fake news by buzzers. This research is a type of normative research. So it can be seen that the threat of punishment that haunted the buzzers spreading hoaxes in the 2019 elections in the Criminal Code is regulated in several articles. The articles in question are Articles 137, 207, 208 paragraph 1, and Article 310 paragraphs 1 and 2. And for stakeholders who order such action from the buzzers, they are threatened with punishment as stipulated in Article 55 paragraph 1 and Article 56 paragraph 1 and 2.